THE CURRICULUM DEVELOPMENT TO ENHANCE COMPETENCIES IN THE ACTIVE LEARNING WITH BRAIN BASED LEARNING TO IMPROVE THE GRADE 1 ELEMENTARY PUPIL’S THAI LITERACY FOR NON-THAI MAJOR TEACHERS - Jitchayawanit, Kulisara (Journal of Social Science and Cultural, 2023)
The purposes of this research were 1) to study of the problems of Thai language learning management 2) to create and examine the quality of the curriculum 3) to try out the curriculum and 4) to assess the curriculum using research and development with 4 steps. The experimental group used in the research was 25 grade 1 Thai language teachers. The research instruments were questionnaires, the assessment forms, test, curriculum and course documents. The statistics used for data analysis were mean, standard deviation, t–test, and content analysis. The results showed that 1) the problematic state of Thai language learning management was at a high level 2) a course consisted of reasons and necessity, principles, aims, content, learning activities, learning materials measurement and evaluation syllabus and course materials. The curriculum and course materials were appropriate at the highest level 3) the results of the try-out curriculum showed that non-Thai major teachers had knowledge and understanding of active learning management after the development was higher than before at the .05 level of statistical significance. Teachers were able to manage active learning based on the brain-based learning. The students’ literacy in Thai abilities after the development was higher than before at the .05 level 4) The results of the curriculum assessment found that the curriculum were appropriate at the highest level.